Navigating Complexity in Future Tourism Metaverses: A Review of Requirements, Designs, and Interactions - Gochhait, Saikat (Journal of Tourism Sustainability, 2025)
The development of shared value in the metaverse and the transformation of perspectives and benefits arising from its advent, especially in tourism, is a domain of research that this paper aims to contribute to. With the above observation of future tourism metaverses, this research attempts to describe the complexity of requirements, designs, and interactions that should be considered for future tourism metaverses towards experiencing the importance of metaverse in tourism. We report findings from a systematic literature examination of 82 peer-reviewed papers published in the Scopus databases, using terminology including but not limited to tourism, tourist, holiday, vacation, hospitality, and metaverse. The research results show that the metaverse can drastically change tourism by providing virtual, hyper-realistic experiences to complement physical journeys. The attributes of metaverse tourism, including stimulus modalities, strength in accessibility, interactivity, amenities, activities, ancillary services, etc., are identified in this work as being vital for maximizing customer satisfaction and engagement. Explore virtuality before reality: Virtual reality (VR), augmented reality (AR), or mixed reality (MR) allows tourists to go through destinations virtually prior to a physical visit; these advancements support better travel planning and decision-making. Moreover, it highlights the significance of inclusive design and adaptive technologies to enhance accessibility to metaverse tourism for diverse audiences. This research contributes to theoretical and practical context throughout the discourse of employing the metaverse for digital marketing, branding, and revenue generation but also integrates environmental aspects of travel through the reduction of related emissions. The implication that emerges from examining the complex requirements and design of metaverse tourism can lay the groundwork for future research and projects in this work area in an interdisciplinary, collaborative, and human-centered design approach.